(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This research analysis and optimizes the main wind horizontal turbine blade parameters for high-performance altitude with variable pitch blade angle for different blade cross-section unsymmetrical airfoil NACA 4412 and unsymmetrical airfoil supercritical Eppler 417. For deep specification, some wind horizontal turbine parameters kept constant through the proses method to integrate the highest behavior of windmill turbine power coefficient. The procedure analysis with FORTRAN.90 code ,then compare with German code and then optimized using Schmitz and Betz method for blade chord and lift to drag for blade pitch angle. From theoretical results discussion, important conclusions figured; also a recommendation for further work was suggested. Best optimization methods were Schmitz chord optimization and Lift/Drag twist optimization which increases the Cp 10.3% for Eppler 4417 and 9.5% for NACA 4412.All results were tabulated and plotted for all optimization results